Reception through Polemics: The Internalization of Theological Otherness in Jerome’s Heresiology - Pålsson Katarina (De Gruyter, 2021)
Early Christian heresiology is, like polemics in general, a genre that has commonly been negatively perceived in scholarship. There is an idea of heresiological texts as not only historically unreliable, but also unproductive, in contrast to the creative thinking that can be found in theological treatises. Considering the understanding of heresiology as reactive and exclusive, it is not surprising that heresiological works have seldom been examined in reception studies. The present article wants to challenge the idea of heresiological work as merely rejecting heresies in the defence of a pre-existing orthodoxy, by applying a dialogical reading to the work Adversus Iovinianum by Jerome of Stridon, a treatise in which he defended the superiority of virginity over marriage against Jovinian’s idea of the equality of all the baptized. Building on the understanding of dialogue expressed by Mikhail Bakhtin, as well as his concept of hybridity, the article analyses how Jerome, instead of simply rejecting core elements of Jovinian’s ideas, such as the goodness of marriage and the natural condition of human beings, rather reappropriates them and integrates them into his making of orthodoxy. The result is a hybrid construction in which anti-ascetic arguments are integrated in a rhetoric of asceticism.